ENHANCEMENT OF STUDENTS CRITICAL THINKING SKILL IN FUNGI CONCEPTS BASED ON SCIENCE, TECHNOLOGY, AND SOCIETY LEARNING APPROACH - Aida Fikriyah; Tjandrakirana Tjandrakirana; Rudiana Agustini (Universitas Negeri Surabaya, 2020)
This study aimed to evaluate the enhancement of students critical thinking in fungi concepts based on Science, Technology, and Society learning approach. The learning process involved a single class consisting of 30 students on the first grade of State Senior High School of 16 Surabaya as the subject of this study. One group pre-test and post-test design was used in the learning process to determine the enhancement of students critical thinking skill. The findings indicated that critical thinking skill on students boosted highly as the effect of the learning process. It can be concluded that Science, Technology, and Society learning approach is able to increase the students critical thinking skill in fungi concepts.